ENERGY EFFICIENT MOTH FLAME OPTIMIZATION ALGORITHM FOR WIRELESS SENSOR NETWORK (International Journal of Food and Nutritional Sciences, 2022)
Sensor Nodes play a vital role in wireless sensor networks (WSN). Routing protocols helps to enhancethe lifespan and energy efficiency of battery powered sensor nodes. In wireless sensor network similarnodes are grouped to form clusters. Moth flame optimization algorithm is used for selecting the clusterhead. MFO algorithm helps to solve the complex real-world problems. In this paper, we propose Mothflame optimization algorithm for Wireless sensor network. This paper presents the steps to form theclustering network in WSN and the transmission strategy.